New species of the anthiadin genus Sacura (Perciformes: Serranidae) from the Andaman Sea - Motomura, Hiroyuki; Yoshida, Tomohiro; Vilasri, Veera (Zootaxa, 2017)
Sacura sanguinea n. sp. (Serranidae: Anthiadinae) is described on the basis of two male and one female specimens from the Andaman Sea. The new species is characterized by the following characters: dorsal-fin rays X, 15; pored lateral-line scales 34; gill rakers 8 + 23 = 31; body depth 42.6–44.7% of SL; head length 39.5–41.4% of SL; pectoral-fin length 32.4–33.1% of SL; poorly defined broad yellow band from anterior profile of head to middle of body, the band gradually becoming red around middle of body and ending at caudal-fin base; caudal fin with distinct red spots centrally; and large dark red blotch posteriorly on spinous portion of dorsal fin in females.